Peran Ganda Istri dalam Meningkatan Ekonomi Keluarga (Studi Deskriptif Pekerja Perempuan Peternakan Ayam Petelur di Desa Kandangan, Kecamatan Srengat, Kabupaten Blitar) - Gatot Anang Marsudi; Kusuma Wulandari; Wahyuni Mayangsari (Pusat Studi Wanita dan Keluarga UGM, 2023)
Social welfare problems arise because basic needs are not met due to the relatively small income of the husband. Most of the women who are in the laying hen farm environment choose to become laying hen farm laborers, due to low levels of education, limited employment opportunities, limited skills This study aims to describe and analyze the dual role of wives in improving the family economy. The approach in this research is qualitative with descriptive study research type. The technique of determining informants using purposive sampling with seven main informants and eight additional informants. Data collection techniques include observation, interviews, and documentation. The results of this study describe the dual role of wives in improving the family economy which is divided into three, namely the dual role of wives, factors that influence the dual role of wives, and the role of wives in improving the family economy. The role of wives as laying hen farm laborers is influential in improving the family economy because the income received by the husband is felt to be unable to meet daily, so the wife wants to help earn additional income. With an increase in the family economy by 2.32% from before, the family welfare can be said to have increased.